A retrospective analysis of recurrent intracranial ependymoma. Issue 7 (24th February 2014) - Antony, Reuben; Wong, Kenneth E.; Patel, Moneil; Olch, Arthur J.; McComb, Gordon; Krieger, Mark; Gilles, Floyd; Sposto, Richard; Erdreich‐Epstein, Anat; Dhall, Girish; Gardner, Sharon; Finlay, Jonathan L.
<x xml:space="preserve">Abstract</x> Background Recurrence occurs in almost 50% of patients with intracranial ependymoma, and their outcome following recurrence is poor. Methods We retrospectively reviewed the medical records of 22 patients with intracranial ependymoma and subsequent relapse(s) (59 recurrences) treated at Children's Hospital Los Angeles or New York University between January 1997 and December 2012. Results Median duration of follow‐up was 52 months (7–171 months). Median age at initial diagnosis was 4 years (0.3–19 years) with 8 patients younger than 3 years at presentation. Eleven patients had anaplastic and 11 cellular pathologies. Eighteen patients had infratentorial tumors at diagnosis and 3 (all infratentorial) had metastatic spinal cord involvement at presentation. Cerebrospinal fluid involvement was not identified at diagnosis or relapse. Median time to first recurrence was 16 months (1.3 to 115 months). The number of recurrences in each patient ranged from 1 to 9 (median = 2). Thirty‐seven recurrences (63%) were detected asymptomatically by surveillance imaging. Fifteen recurrences (26%) arose outside the initial tumor site. Recurrences were treated by surgical resection (45), with irradiation (30), and with various oral chemotherapies (23) with (7) or without (16) conventional chemotherapy. The 5 and 10 year overall survival rates from first recurrence were 0.37 ± 0.14 and 0.25 ± 0.14. Conclusion Prolonged (5–10 year) survival from first relapse was noted in over one‐quarter of our patients. It remains unclear whether early radiographic diagnosis, differing treatment modalities beyond radical surgical resection or possibly unrecognized biological differences contributed towards this prolonged survival. Pediatr Blood Cancer 2014;61:1195–1201. © 2014 Wiley Periodicals, Inc.